Fatty acids as biological markers for symbiotic bacteria in Phyllidia varicosa and Phyllidiella pustulosa - Alqudah, Ali; Saad, Shahbudin; Darnis, Deny Susanti; Nordin, Noor Faizul Hadry (Malaysian Society of Applied Biology, 2016)
The fatty acid (FA) composition of Phyllidia varicosa and Phyllidiella pustulosa (notum and viscera) was investigated. Samples were collected from coastal water of Balok - Pahang - Malaysia. This study was conducted to test the hypothesis that nudibranchs species host symbiotic bacteria by using fatty acids as biological markers. A high level of fatty acids group specific to the bacteria were detected in the selected species that called odd- branched chain fatty acids. Among them, high levels of iso- anteiso-C15:0, C15:0, iso-C16:0, C17:0, iso-C17:0, iso C17:1(n-5), iso C18:0, 14-methyl-C18:0 and iso-C18:0) were found and their percentages in the notum are significantly different compared to viscera. The total odd- branched chain fatty acids were 29.64% in P. varicosa and 30.66% in P. pustulosa compared to another group of fatty acids such as saturated FA, monounsaturated FA and polyunsaturated FA. The present study deals with the identification of cyclopropane FA in the nudibranch tissue for the first time which cyclopropaneoctanoic acid 2-hexyl and cyclopropaneoctanoic acid 2-octyl were detected. We suggest that symbiotic bacteria associated with the nudibranchs tissue originate these fatty acids.